EFISIENSI EKONOMI SEBAGAI REMEDY HUKUM - Sugianto, Fajar (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2013)
Law and Economics as a branch of Jurisprudence offers economic efficiency as a legal norm that guides the activities of the law. Under proper coceptualization, economic efficiency also helps to examine, evaluate, as well as valuating law and the jurisprudence. In this paper, one of the forms of economic efficiency is applied as the economic approach to law to distribute in which the law must be able to stipulate all the profit produced. In this case, economic efficiency made the law as an incentive to alter behavior as well as directing and maintaining them in accordance with the purpose of the law. The remedy of law through economic efficiency aims at revealing important aspects as the essence of definitive foundation ofÂ jurisprudence.Key words: Â economic efficiency, incentive, remedy.